THE GRADUAL CLASSIFICATION OF THE FRENCH CONSONANT SYSTEM BASED ON THE PARTICIPATION OF THE ARTICULATORY ORGANS IN PRONUNCIATION (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores the gradual classification of the French consonant system with respect to the involvement of the vocal folds in articulation. The study focuses on the phonetic principles underlying consonant production and examines how the participation of the vocal folds contributes to the systematic organization of consonant sounds. Special attention is given to the articulatory features that distinguish voiced and voiceless consonants within the French phonological system. The analysis aims to clarify the theoretical foundations of consonant classification and to contribute to a deeper understanding of French phonetics.
Keywords: gradual relations, consonant phonemes, consonant paradigm, voiced and voiceless consonants, anterior (front) consonants, posterior (back) consonants, articulatory features, acoustic features.